The study’s ability to acquire acidity refractory metals in liquid nickel by electromotive force - Шаркіна, Н.О. (Proceedings of National Aviation University (archive), 2009)
The method of EMF with the hard electrolyte of oxide is get thermodynamic given for system of Ni – O – M (M – IVb-VIb- metals). It is set that the row of metals is reduced by activity of oxygen, that conditioned them by a strong cognation with oxygen. It is set that by the products of reoxidation more frequent all there are stable oxides of the proper metals.